International symposium: International Symposium for Asian Management of Technology Education (ISAME2021) - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2021)
The International Symposium for Asian Management of Technology Education (ISAME2021) was held as a virtual event on 1–2 September 2021. The symposium was organized by the Asia Innovation Center (AIC) and Yamaguchi University Management of Technology (YUMOT), Japan, in collaboration with several partner institutions, including the Arshad Ayub Graduate Business School (AAGBS), Universiti Teknologi MARA (UiTM). The symposium served as a platform for academics, researchers, and practitioners to exchange ideas and insights on issues related to the management of technology education in Asia.